2013
DOI: 10.1007/s10552-012-0130-8
|View full text |Cite
|
Sign up to set email alerts
|

Indoor air pollution and risk of lung cancer among Chinese female non-smokers

Abstract: Purpose To investigate indoor particulate matter (PM) level and various indoor air pollution exposure, and to examine their relationships with risk of lung cancer in an urban Chinese population, with a focus on non-smoking women. Methods We conducted a case-control study in Taiyuan, China, consisting of 399 lung cancer cases and 466 controls, of which 164 cases and 218 controls were female non-smokers. Indoor PM concentrations, including PM1, PM2.5, PM7, PM10 and TSP, were measured using a particle mass moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(112 citation statements)
references
References 51 publications
(40 reference statements)
2
102
0
Order By: Relevance
“…The association was strongest in women with both coal use and poor kitchen ventilation during both childhood and adulthood. Consistent with previous studies 24, 3037 , poor indoor air quality was found to elevate lung cancer risk in our prospective cohort study. Conversely, we observed no elevated lung cancer risk associated with cooking oil use.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The association was strongest in women with both coal use and poor kitchen ventilation during both childhood and adulthood. Consistent with previous studies 24, 3037 , poor indoor air quality was found to elevate lung cancer risk in our prospective cohort study. Conversely, we observed no elevated lung cancer risk associated with cooking oil use.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies on fuel use, ventilation, indoor air quality, and lung cancer risk were case-control studies 24, 3037 . However, few studies were conducted in urban areas where rapid socioeconomic development led to substantial modernization in kitchen ventilation and fuel use 30, 31, 37 .…”
Section: Introductionmentioning
confidence: 99%
“…12, 13). Exposure to indoor air pollution is thought to account for unexpectedly high rates of lung cancer among some populations with a low smoking prevalence, such as Chinese women (14).…”
Section: Lung and Bronchusmentioning
confidence: 99%
“…Approximately, half of the world's population is at risk of developing respiratory diseases due to the use of unprocessed biomass fuel and coal for cooking and heating (10,11). A previous study conducted in China demonstrated that indoor air pollution has an important role in the development of lung cancer among Chinese women, particularly among never-smokers (9).…”
Section: Aetiology Of Lung Cancermentioning
confidence: 99%
“…However, the exact genetic mechanisms influencing lung cancer susceptibility in female relatives in China are unknown (89). Indoor cooking is still practiced in some rural areas of China and in numerous other countries; this practice can be considered an important risk factor for lung cancer among women (11). The abovementioned studies suggest that lung cancer is likely to develop in genetically predisposed individuals.…”
Section: Familial Lung Cancermentioning
confidence: 99%